Penser et écrire l’histoire d’un Moyen Âge en Afrique - Claire Bosc-Tiessé (Afriques)
This reading note shows how François-Xavier Fauvelle-Aymar, in his book Le rhinocéros d’or. Histoires du Moyen Âge africain, aims to renew both our perception of the documents and our manner of describing the history of Medieval Africa. Above all, it highlights the underlying purpose of the book, to define an African Middle Age in function of the global history, here in relationship to changes in the Muslim world, and how the author proceeds in the construction of his proposition.